Cell-mimicking nanolipogel for encapsulation & delivery of SPARC siRNA - Muhammad Aminuddin Anuar (2019)
The advancement in the biomedical arena witnessed various effective therapeutic agents being developed to combat various diseases. In recent years, nucleic acid agents have attracted attention as the next generation therapeutics. The driving force for using RNA interference (RNAi) as an alternative therapy is due to its highly selective targeting through base-pair interactions, unrestricted choice of targets, minimal side effects and costeffectiveness compared to protein therapies. However, this technology has its own limitations. To overcome its drawbacks, an effective drug delivery system is needed to deliver the administered therapeutic to its intended site. In this study, cross-linked nanolipogel (NLG) particles containing Chitosan Methacrylate Anhydride (Chitosan-MA) and SPARC small interfering RNA (siRNA) were designed and fabricated in the effort to prolong the administered therapy. The formulated NLG particles were characterised and found to be spherical with diameter of 139.6 ± 0.76 nm. Following that, siRNA release study was conducted on the NLG over 28 days. From the release study, it was observed that the cross-linked NLG particle could sustain release siRNA over 28 days. The remaining SPARC siRNA within the NLG suggested potential release profile to be more than 28 days. A 14-day cell toxicity study conducted showed 0.03125mM NLG to be the suitable dosage for subsequent in vitro studies. Qualitative and quantitative cell studies conducted to observe NLG entry into Human FibroGRO fibroblast cells showed 20 % cell entry after 1-day of NLG treatment. This study validated that the NLG system developed could not only efficiently encapsulate siRNA, but also sustains release siRNA over 28 days without drastically hindering cell proliferation.